Kontekstualisasi Nilai-Nilai Al-Qur’an Perspektif Kebijakan Penyelenggaraan Pendidikan Telaah Normatif Empiris Program PengajaranSatuanPendidikan Pondok Pesantren Tahfidzul Qur’an Ibnu Ali Pamekasan - NUR ISKANDAR; Jatim Jatim; Hendri Masduki (El-Furqania : Jurnal Ushuluddin dan Ilmu-Ilmu Keislaman, 2023)
Contextualization of the values ​​of the Qur'an is a policy perspective in the implementation of education which is directed at developing the potential of students so that they have the ability to associate; interact; and constructing social reality as an instrumental spectrum in the continuity of the learning process in units educational. This policy is believed to be a key instrument that is considered effective and systemic in determining the success of the formation of the minimum competencies that students must possess through the provision of education that refers to the principle of active learning; innovative; creative; educative; and fun both at the normative level and at the empirical level. Keywords :Contextualization of Al-Qur'an Values, Implementation of Education.